Magi. 3 : the labyrinth of magic - Otaka, Shinobu; Werry, John (Translator) (Viz Media, 2013)
"Aladdin finds himself among the Kouga tribe, who live deep in the desert far from Qishan. An emissary from the Kou Empire arrives offering peace, but when it turns out to be an offer they can't refuse, things take a turn for the worse. Aladdin learns more about the legend of the Magi and the Rukh, bird-like beings of light, with whom he appears to share a deep connection" --